The trauma of the main character in the Tattooist of Auschwitz by Heather Morris - Pramudya, Damar Asa; Luthfia, Karina Hanum (EduLite: Journal of English Education, Literature and Culture, 2025)
This research attempts to see the forms of trauma experienced by the main character of the novel The Tattooist of Auschwitz and how he responds to it. Methodologically, this research was under a descriptively qualitative method supported by the psychological approach of post-memory. The primary data was from The Tattooist of Auschwitz novel. The technique to collect the data used a heuristic reasoning technique. The findings of the study found that there are two forms of trauma, namely physical and psychological trauma. Physical trauma is in the form of injuries, vomiting, and trembling, while psychological trauma is in the form of fear, nervousness, anger, and sadness. There are four main characters’ responses in this novel: emotional, cognitive, behavioral, and physical. The emotional response in this novel is in the form of panic, refusal, and avoidance, and the cognitive response in this novel is in the form of difficulties in concentrating. The behavioral response in this novel is in the form of avoiding people and talking about the experiences. The physical response is related to the physical act committed by someone who suffers from the trauma. The physical response in this novel is in the form of losing the body’s strength. By examining these layers of trauma and response, the study underscores the complex interplay between body and mind in the aftermath of profound suffering. This analysis offers a deeper understanding of how trauma shapes human behavior and emotions, providing insight into the broader psychological impacts of extreme adversity.